No policy is an island - on the interaction between industrial and other policies - Timo Välilä (EIB Papers, 2006)
Considering industrial policy from the perspective of other economic policies, this paper seeks to identify the sources and consequences of conflicts between industrial, competition, trade, and fiscal policies. The goals of industrial policy, even when economically justified in isolation, are in certain circumstances in an intrinsic conflict with especially competition and trade policy goals. Industrial policy also lacks its own independent instruments, and fiscal policy instruments are frequently used and often economically optimal to implement industrial policy, which can create a policy conflict even when the goals themselves are independent. For these reasons, the cost of industrial policy is often the sacrifice of some other policy goal. This interdependence narrows the scope for economically sensible industrial policy.
Keywords: 330; Industriepolitik; Wirkungsanalyse; Wettbewerbspolitik; Außenhandelspolitik; Theorie; EU-Staaten